Health and Wellbeing of Clinical Dental Care Professionals: A Systematic Review. Issue 2 (June 2022) - Kaki, Layan; KC, Sukriti; Gallagher, Jennifer E.
Background: There has been much research relating to stressors in the dental environment and concerns over dentists' health and wellbeing. The determinants of dentists' health and wellbeing within the UK include macro- factors, such as healthcare systems and regulation; meso- factors, such as job specification and workplace characteristics; and micro- factors, such as personal aspects, professional career level, and personal and professional relationships. Given the challenges in dentistry, research is needed to investigate the key determinants relating to the health and wellbeing of clinical dental care professionals (DCPs) nationally. Aim: To review the literature on the key determinants of health and wellbeing among dental hygienists, dental therapists, clinical dental technicians, and orthodontic therapists in the UK. Materials and methods: A systematic review of the literature was conducted across seven databases. The records were screened by title, abstract and full text based on the study inclusion criteria. Extraction of data and a qualitative synthesis of the included studies was performed. A mixed methods appraisal tool was used to quality assess for risk of bias. Results: Twelve studies were included in this review, eleven of which were medium to high quality (5*, 4*) and one low quality (2*). Ten studies focused on dental therapists, and/or hygienists, with only one each on orthodontic therapists and clinical dental technicians. Job satisfaction and professional careers were the primary factors explored in the included studies and clearly identified as determinants of health and wellbeing. However, there was evidence of these being associated and linked with a range of determinants at macro-, meso-, and micro-levels, with a general lack of evidence on the overall health and wellbeing. Conclusion: There is currently very limited evidence on the key determinants of health and wellbeing of clinical DCPs within the UK, but the available evidence maps to the same domains as dentists. Further well conducted research examining the overall health and wellbeing is required, with consideration of the full matrix of possible factors.